Listeria monocytogenes at the interface between ruminants and humans: A comparative pathology and pathogenesis review. Issue 2 (March 2022) - Bagatella, Stefano; Tavares-Gomes, Leticia; Oevermann, Anna
The bacterium Listeria monocytogenes ( Lm ) is widely distributed in the environment as a saprophyte, but may turn into a lethal intracellular pathogen upon ingestion. Invasive infections occur in numerous species worldwide, but most commonly in humans and farmed ruminants, and manifest as distinct forms. Of those, neuroinfection is remarkably threatening due to its high mortality. Lm is widely studied not only as a pathogen but also as an essential model for intracellular infections and host-pathogen interactions. Many aspects of its ecology and pathogenesis, however, remain unclear and are rarely addressed in its natural hosts. This review highlights the heterogeneity and adaptability of Lm by summarizing its association with the environment, farm animals, and disease. It also provides current knowledge on key features of the pathology and (molecular) pathogenesis of various listeriosis forms in naturally susceptible species with a special focus on ruminants and on the neuroinvasive form of the disease. Moreover, knowledge gaps on pathomechanisms of listerial infections and relevant unexplored topics in Lm pathogenesis research are highlighted.